Analysis of borehole breakout development using continuum damage mechanics. (September 2017) - Sahara, David P.; Schoenball, Martin; Gerolymatou, Eleni; Kohl, Thomas
Abstract: Damage distribution and evolution have a significant effect on borehole stress concentrations. To model the complex fracturing process and inelastic deformation in the development of the borehole breakout, we implement a continuum damage mechanics (CDM) concept that takes tensile and compressive failure mechanisms into account. The proposed approach explicitly models the dissipative behavior of the material due to cracking and its evolution, which leads to an inhomogeneous redistribution of material properties and stresses in the vicinity of the borehole wall. We apply a constitutive plastic model for Berea sandstone and compare our numerical results to laboratory experiments performed on Tablerock sandstone. We are able to reproduce several characteristics of the failure process during the breakout development as observed in experimental tests, e.g. localized crack distribution in the vicinity of the borehole wall, damage evolution, which exhibits a widening process in the beginning followed by subsequent growth in depth, and shear fracturing-dominated breakout growth in sandstone. A comparison of our results with laboratory experiments performed on a range of stress conditions shows a good agreement of the size of borehole breakouts. The importance of the constitutive damage law in defining the failure mechanisms of the damaging processes is discussed. We show that the depth and the width of breakouts are not independent of each other and no single linear relation can be found between the size of breakouts and the magnitude of the applied stress. Consequently, only one far field principal stress component can be estimated from breakout geometry, if the other two principal stresses are known and sufficient data on the plastic parameters are available. Highlights: Implementation of CDM concept to model breakout in an elastoplastic material Reproduce key characteristics of the transient failure as observed in experimental tests A good agreement between our numerical model and experimental tests Relation between the magnitude of the far field stresses and the size of breakouts